Advanced Digital Technologies and Investment in Employee Training: Complements or Substitutes? - Giorgio Brunello; Désirée Rückert; Christoph T. Weiss; Patricia Wruuck (Institute of Labor Economics (IZA), 2023)
Using firm-level data covering the 27 EU countries, the UK and the US, we show that employers tend to reduce investment in training per employee after adopting advanced digital technologies (ADT). We estimate with a control function approach firm-level production functions augmented with two factors, the training stock per employee and digital technology use. We show that ADT use and employee training are substitutes in production, implying that an increase in the former negatively affects the marginal productivity of the latter, and that a decline in the cost of introducing ADT reduces employers' investment in training per employee. These findings point to challenges in realizing high levels of firm-sponsored training for employees in increasingly digital economies.
Keywords: D24; J24; 330; digitization; automation; training; productivity